A Clinical Study of the Safety and Tolerability of Live Nasal Vaccines for the Prevention of Pertussis - A. Yu. Medkova; A. A. Lidzhieva; E. G. Semin; L. N. Sinyashina; R. A. Sioundioukova; I. N. Dyakov; L. V. Kolobukhina; I. S. Kruzhkova; L N. Merkulova; M. G. Rusanova; N. A. Antipyat; S. V. Smetanina; et al. (Разработка и регистрация лекарственных средств, 2021)
Introduction. Due to the growth of laboratory-confirmed cases of pertussis among adolescents and adults, the spread of latent form of disease and the identification of asymptomatic carriage of the pathogen, the need arose to create a new vaccine against B. pertussis. On the basis of N. F. Gamaleya Federal Research Center for Epidemiology & Microbiology, a pertussis vaccine, containing attenuated B. pertussus bacteria, was developed. The article presents data on a clinical trial of the first phase of the pertussis vaccine “GumGVK, live intranasal vaccine for the prevention of pertussis” in healthy volunteers. Based on the results of the study, data shows the safety and tolerability of the first intranasal vaccine using on humans.Aim. To Study the safety and tolerability of the vaccine "GamGVK, live vaccine for intranasal use for the prevention of whooping cough»Materials and methods. Volunteers who expressed a desire to participate in the study were informed about its goals and objectives, conditions and requirements for participants, including the criteria for their inclusion/exclusion from the study. After signing the informed consent, the volunteers were screened for their compliance with the inclusion criteria. Screening studies and safety assessment of the drug were performed on the basis of anamnesis, subjective complaints, assessment of vital signs, ECG, peak flowmetry, results of laboratory tests of urine and blood, enzyme immunoassay of blood serum, analysis of nasopharyngeal aspirates for the presence of pertussis pathogen DNA, results of physical examination.Results and discussion. The study involved 36 "healthy" volunteers aged 18–40 years. The average age of the volunteers was 26.2 ± 5.5 years. Not reliably identified AES associated with the use of GumGVK. None of the used doses of the drug led to the formation of local and General allergic reactions to intranasal administration of GumGVK.Conclusions. The drug GumGVK is safe for nasal use, has good tolerance.